StudiIn SilicoSenyawaTurunan8-Tersubtitusi-7-Methoxy-2h-Chromen-2-OneSebagaiPenghambatEnzim Telomerase - Tahir, Masdiana; Damayanti, Sophi; Hadi, Daryono; Tjahyono, Tjahyono (Jurnal Farmasi Indonesia, 2018)
Adjustment of telomere length by telomerase is considered as a biological marker which determine the proliferation of cancer cells. The telomerase activity in cancer cells is potential to be targeted for cancer therapies. The aim of this study was QSAR studies to determine the descriptors that affect the anticancer activity of 8-substituted-7-methoxy-2H-chromen-2-one derivatives. The descriptors were calculated by using software MOE® 2009.10. to design new derivative compounds that have anticancer potency, to predict pharmacokinetic properties by using preADMET, and to predict tocixity by ADMET predictorTM and interaction predict to telomerase by using Autodock 4.2.6  The results showed QSAR equation was log IC50 = -1.358 (± 1.149) - 2.957 (± 1.019) × AM1_LUMO + 0.041 (± 0.011) × E_vdw + 2.367 (± 0.748) × glob + 0.487 (± 0.100) × log S. Fourteen of the new derivative compounds were designed based on QSAR equation revealed higher activity prediction than the lead compound and performed good absorption in the intestine. Compound (33) is predicted to have low permeability in Caco-2 cells and weakly bound to plasma proteins. Compound (50) predicted weakly bound to plasma proteins as well. Toxicity prediction showed that 9 derivatives compounds were predicted to have lower nearly equal toxicity to the toxicity of the lead compound. The study of the interaction of compounds with the receptor showed that derivatives (2), (4), (40) and (41) have the highest affinity to the receptor TERT with the binding free energy is −9.60 kcal / mol, −9.39 kcal / mol, −9.20 kcal / mol and -9.08 kcal / mol. Based on QSAR study, pharmacokinetic profile, toxicity, and the study of the interaction, four compounds have the potential to be develop as anticancer with telomerase inhibition.